Antioxidants Associated With Oncogenic Human Papillomavirus Infection in Women. (18th March 2021) - Lin, Hui-Yi; Fu, Qiufan; Kao, Yu-Hsiang; Tseng, Tung-sung; Reiss, Krzysztof; Cameron, Jennifer E; Ronis, Martin J; Su, Joseph; Nair, Navya; Chang, Hsiao-Man; Hagensee, Michael E
Abstract: Background: Human papillomavirus (HPV) infection is a major cause of cervical cancer. Studies showed the onset of HPV carcinogenesis may be induced by oxidative stress affecting the host immune system. The association between antioxidants and oncogenic HPV remains unclear. In this study, we aim to identify antioxidants associated with vaginal HPV infection in women. Methods: The associations between the 15 antioxidants and vaginal HPV infection status (no, low-risk [LR], and high-risk [HR] HPV) were evaluated using 11 070 women who participated in the 2003–2016 National Health and Nutrition Examination Survey (NHANES). Results: We identified serum albumin and 4 dietary antioxidants (vitamin A, B2, E, and folate) inversely associated with HR-HPV infection. Women with a low level of albumin (≤39 g/L) have a significantly higher risk of HR-HPV (odds ratio [OR] = 1.4, P = .009 vs >44 g/L). A Nutritional Antioxidant Score (NAS) was developed based on these 4 dietary antioxidants. The women with the lowest quartile NAS had a higher chance of HR-HPV (OR = 1.3, P = .030) and LR-HPV (OR = 1.4, P = .002) compared with the women with the highest quartile NAS. Conclusions: We identified 5 antioxidants negatively associated with vaginal HR-HPV infection in women. Our findings provide valuable insights into understanding antioxidants' impact on HPV carcinogenesis. Abstract : Serum albumin and 4 dietary antioxidants (vitamin A, B2, E, and folate) were inversely associated with high-risk HPV vaginal infection. The nutritional antioxidant score based on these 4 dietary antioxidants was also inversely associated with high-risk and low-risk HPV infection.